Аmygdala DEGs are associated with the immune system function: A comparative transcriptomic study of high- and low-excitability rat strains - Irina Shalaginova; Marina Pavlova; Natalia Dyuzhikova (PLoS ONE, 2025)
The aim of this study was to investigate differentially expressed genes (DEGs) in the amygdala of Rattus norvegicus with contrasting levels of nervous system excitability (high- and low-excitability). Each group consisted of 5 intact rats (n = 5). RNA sequencing was performed at on a HiSeq1500 (Illumina) generating at least 20 million paired-end reads per sample. A total of 257 DEGs were identified: 152 genes were upregulated in high-excitability rats and 105 genes up-regulated in low-excitability rats. Gene Ontology (GO) and KEGG pathway analyses revealed that the differences in gene expression were associated with immune processes such as antigen presentation and regulation of inflammation. It is also discussed, in conjunction with previous findings, that high-excitability rats may exhibit a predisposition to increased neuroinflammatory activity even without stressor exposure, potentially contributing to varying behavioral responses to stress.